Quality of Tea Fermented Drink from Natural Fermentation of Banana (Musa paradisiaca) and Fuji Apple (Malus domestica) - Karina Bianca Lewerissa; Monika Rahardjo; Regina Natasya Budi; Rafaelle Jovanka; Bintang Carouline (Soegijapranata Catholic University, 2025)
Bananas and apples are fruits that are easily found in Indonesia. Those fruits are sometimes wasted during peak seasons. This research aims to increase the additional value of bananas and apples by using them as a starter for fermented tea drinks. Twenty percent of bananas and apples (1:1 ratio) were immersed in a 5% sucrose solution at room temperature. The solution was stirred daily and harvested after 72 hours of fermentation. Results show that the resulting starter contained 2.9 x 1011 CFU/ml lactic acid bacteria with 83 + 9.5% lactic acid content and a total of 1.7 x 1012 CFU/ml microbes. The pH of the starter was 3.7 + 0.1. Microscopic observations show that most microorganisms were yeast and Gram-positive bacteria (rod and sphere). The starter was then diluted into tea drinks sweetened by glucose 10% with four types of dilution ratios, namely a ratio of 1:5, 1:10, 1:15, and 1:20 (tea: starter). The organoleptic tests on 20 untrained panelists showed that the most preferred tea was the one with 15 times dilution in terms of taste, aroma, and color. The number of lactic acid bacteria in fermented tea with a 1:15 ratio still met the requirements of a probiotic drink.